Spread patterns and effectiveness for surgery after ultrasound-guided rectus sheath block in adult day-case patients scheduled for umbilical hernia repair - Alberto Manassero; Matteo Bossolasco; Maurizio Meineri; Susanna Ugues; Chrysoula Liarou; Luca Bertolaccini (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: We conducted a prospective study to examine the local anesthetic (LA) spread and the effectiveness for surgical anesthesia of ultrasound (US)-guided rectus sheath block (RSB) in adult patients undergoing umbilical hernia repair. Material and Methods: Thirty patients received at T-10 level a bilateral US-guided injection of 20 mL levobupivacaine 0.375% + epinephrine 5 μg/mL behind the rectus muscle to detach it from its sheath. Anesthetic spread into the rectus sheath was evaluated ultrasonographically at T-9 and T-11 levels and scored from 0 to 4. The RSB was defined effective for surgical anesthesia if it was able to guarantee an anesthetic level sufficient for surgery without any mepivacaine supplementation. Results: Overall, the block was effective for surgical anesthesia in 53.3% of patients (95% confidence interval, ±17.8). In the remaining patients, anesthesia supplementation was needed at cutaneous incision, whereas manipulation of the muscle and fascial planes was painless. No patients required general anesthesia. LA spreads as advocated (to T-9 and to T-11 bilaterally = spread score 4) in 8/30 patients (26.6%); in these cases, the block was 75% effective for surgery. The anesthetic spread was most negatively influenced by increased body mass index. Postoperative analgesia was excellent in 97% of patients. Conclusion: Use of RSB as an anesthetic management of umbilical herniorrhaphy is recommended only with anesthetic supplementation at the incision site.